2021
DOI: 10.3390/technologies9020025
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of iPad Pro®’s LiDAR and TrueDepth Capabilities with an Industrial 3D Scanning Solution

Abstract: Today’s smart devices come equipped with powerful hard- and software-enabling professional use cases. The latest hardware by Apple utilizes LiDAR and TrueDepth, which offer the capability of 3D scanning. Devices equipped with these camera systems allow manufacturers to obtain 3D data from their customers at low costs, which potentially enables time-efficient mass customization and product differentiation strategies. However, the utilization is limited by the scanning accuracy. To determine the potential applic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 14 publications
0
56
0
2
Order By: Relevance
“…Also, the technical features, cost and manoeuvrability of both devices represent an interesting solution when compared to other more consolidated range-based techniques, already employed in various fields, such us Terrestrial Laser Scanning (TLS) or Time of Flight (TOF) cameras (Chiabrando et al, 2011). The new iPad Pro could be compared to recently studied sensors not specifically developed for 3D metric survey; cameras embedded in smartphones are tested for metric reconstruction as low cost and rapid solutions in case of complex environment as underground cave (Dabove et al, 2019) or for small objects (Vogt et., 2021). Other studies are focused on flexible and light weight mobile mapping systems built-in tablet, as in the case of an object survey with the Lenovo tablet (Donlic et al, 2017), or wearable instrument, as the Microsoft Hololens tested for metric survey of architectures (Khoshelham et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Also, the technical features, cost and manoeuvrability of both devices represent an interesting solution when compared to other more consolidated range-based techniques, already employed in various fields, such us Terrestrial Laser Scanning (TLS) or Time of Flight (TOF) cameras (Chiabrando et al, 2011). The new iPad Pro could be compared to recently studied sensors not specifically developed for 3D metric survey; cameras embedded in smartphones are tested for metric reconstruction as low cost and rapid solutions in case of complex environment as underground cave (Dabove et al, 2019) or for small objects (Vogt et., 2021). Other studies are focused on flexible and light weight mobile mapping systems built-in tablet, as in the case of an object survey with the Lenovo tablet (Donlic et al, 2017), or wearable instrument, as the Microsoft Hololens tested for metric survey of architectures (Khoshelham et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The iOS of Apple's smartphones and tablets provides 3D data without the operator's measurement experiences, called TrueDepth Scanner, based on the structure-light principle 1 . TrueDepth-based 3D scanning shows the highest deviations in cylindricity (0.82 mm in average) and roundness (1.17 mm on average) 25 . In another 3D scanning study, Camison et al demonstrated that the points calculated from a total of 136 distances had an average deviation (mm) of 0.84 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, keeping the appropriate HDMM threshold without the new position for CBCT scanning is important for intolerant patients in GKRS frameless xation. 25 . The front-facing camera provides the depth data in real-time along with visual information, and the system uses a light-emitting diode to project an irregular grid of over 30,000 infrared dots to record the depth within milliseconds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It may also be possible to provide software solutions such as augmented reality. Technologies such as LiDAR (light detection and ranging) and TrueDepth [ 66 ], have become available in the latest iPhone and Android phones and tablets; therefore, it may be possible to overlay digital information on limbs and provide more accurate sensor placement instructions for home use.…”
Section: Limitationsmentioning
confidence: 99%